53.8k views
0 votes
HELP ASAP PLEASE!!!!!!!!!!!!!!!!!!!!!!!!!!!

HELP ASAP PLEASE!!!!!!!!!!!!!!!!!!!!!!!!!!!-example-1
User AndyClaw
by
4.8k points

1 Answer

2 votes

Answer:

Option (B)

Explanation:

The given expression is,


√(22x^6)/√(11x^4)

We can rewrite this expression as,


(√(22x^6))/(√(11x^4) )

Solving it further,


(√(22x^6))/(√(11x^4) )=(√(22(x^3)^2) )/(√(11(x^2)^2) ) [Since
x^3* x^3=x^6 and
x^(2)* x^(2)=x^4]


=\sqrt{(22(x^3)^2)/(11(x^2)^2) } [Since
(√(a) )/(√(b) )=\sqrt{(a)/(b) }]


=(x^3)/(x^2)\sqrt{(22)/(11) }


=x√(2)

Therefore, quotient will be x√2.

Option (B) will be the correct option.

User Meetu
by
5.7k points